A novel method has been developed to efficiently recover valuable lead, zinc, and rare earth elements from hazardous waste generated by glass polishing - Azza A. Gabr; Mohamed A. Ali; Ahmed H. Orabi; Hiam M. Osman; Salah S. Elyan (Arab Journal of Basic and Applied Sciences, 2023)
AbstractDiscovering new processing routes to put waste to use in the manufacturing of high-value products is essential to the success of the circular economy. A glass polishing waste containing 16.4% PbO, 0.672% ZnO and 7.296% rare earth elements (REEs) oxides was subjected to this work. The current research looked into the feasibility of adopting a sequential three-stage leaching procedure to selectively recover Pb, Zn, and REEs from hazardous glass polishing waste (HGPW). First-stage leaching with 1 M H2SO4 at 80 °C for 90 min extracted 75–99.9% of contaminant heavy metals such Fe, Ni, Co, and Cu, leaving behind insoluble residue containing the metals of interest. In the second stage of leaching, the sodium hydroxide solution extracted Pb and Zn from the first spend residue. Using shrinking core models, we were able to assess the kinetics of lead and zinc dissolution. The activation energy was determined to be 32.16 kJ/mol for Pb and 34.59 kJ/mol for Zn. In the final step, the REEs were extracted from the dried alkali-treated residue by leaching it with concentrated H2SO4 at higher temperatures. For the technological recovery of Pb, Zn, and REEs from glass polishing waste, a flow chart was created.